SOSIALISASI GREEN PACKAGING DI DESA DARMAWANGI KECAMATAN TOMO KABUPATEN SUMEDANG - Yosini Dekiana; Sri Fatimah; Lucyana Trimo; Mohamad Djali; Endah Wulandari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
To overcome plastic waste, the Government of Indonesia has issued Presidential Regulation No. 83 of 2018. Also Bandung Regional Regulation No. 17 of 2018 on reducing the use of plastic bags. A number of strategies have been carried out but until now the implementation has not run optimally. Partners are empowered with training on the importance of green packaging to reduce plastic waste. It is hoped that if the partner has a cohesiveness in managing his business, a strong motivation in entrepreneurship, has a potential product to be marketed, know the green packaging and know the tarket of the green consumer consumer market, then improved the product to green products. Handling the environmental issues of the paper industry through the use of non-wood paper base material becomes an interesting thing by utilizing annual crops or agricultural plant residues to be used as the basic material of paper and pulp. Community service in Darmawangi village, Tomo District, Sumedang regency about green packaging began by giving the material "Socialization of Green Packaging for Mango Soap Products" to a group of women farmers in Darmawangi Village. The material was given online at the Food Security and Security Webinar on June 17, 2020, followed by material on entrepreneurial motivation. Evaluation of PPM activities on green packaging in Darmawangi Village showed good enthusiasm and the increase of about 75% understanding of environmentally friendly packaging.